INDUSTRIAL CONFLICT IN A DEPRESSED ECONOMY: THE EXPERIENCE OF NIGERIA (2012-2024) - John-Williams, Ann Kuro (African Journal of Social and Behavioural Sciences, 2025)
The study examined the impact of industrial conflicts, particularly strikes in an already depressed economy like Nigeria. Two research questions and corresponding objectives were formulated to aid the study. The study is anchored on the Marxian Conflict theory by Karl Marx. The study is a descriptive type of study that uses desk research methodology. Data was sourced from secondary sources through the internet, newspapers, Journals and textbooks for data collection. The study reveals that grievances as a result of low wages, poor working conditions and lack of promotion lead to conflict. Also, conflicts of any nature hamper the growth of any organization or nation. The study concluded that Although Conflict is an essential part of life, it must be treated carefully as any one perspective of conflict (strike) activity can be quite misleading. Several perspectives have to be taken together in order to provide a fair picture and resolve them effectively for the benefit of all parties involved and the economy at large. It, however, recommends, amongst others, that an institutionalisation of industrial democracy is a proactive and corrective mechanism that should be put in place to be able to detect, prevent and correct the possibility of an industrial conflict quickly when it arises.